Literasi Digital dan Skeptisisme Profesional dalam Meningkatkan Kesadaran dan Kemampuan Deteksi Kecurangan pada Calon Akuntan: Systematic Literature Review - Reni Suwandi Ade Puspita (International Forum of Researchers and Lecturers, 2026)
This systematic literature review examines how digital literacy and professional skepticism contribute to fraud awareness and fraud detection among future accountants. The review responds to the increasing digitalization of accounting and auditing, where artificial intelligence, data analytics, and digital audit technologies create both opportunities and new forms of fraud risk. A structured review was conducted on academic publications, prioritizing studies published between 2021 and 2026. Studies were selected when they addressed digital literacy or digital competence in accounting education, professional skepticism, fraud awareness or fraud detection, and technology or artificial intelligence in accounting and auditing. The synthesis indicates three recurring findings. First, digital literacy is increasingly associated with analytical, critical, and technology-related capabilities among accounting students and future professionals. Second, professional skepticism generally strengthens evidence evaluation, recognition of red flags, and fraud-related judgment, although its effect may depend on experience, ethics, organizational support, and audit context. Third, technology can improve fraud detection, but its effectiveness does not eliminate the need for human judgment. The review identifies a research gap in studies integrating digital literacy, professional skepticism, artificial intelligence, and fraud detection within accounting education.